2015
DOI: 10.2131/jts.40.817
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury can induce Parkinson’s-like neurotoxicity similar to 1-methyl-4- phenylpyridinium: a genomic and proteomic analysis on MN9D dopaminergic neuron cells

Abstract: -Exposure to environmental chemicals has been implicated as a possible risk factor for the development of neurodegenerative diseases. Our previous study showed that methylmercury (MeHg) exposure can disrupt synthesis, uptake and metabolism of dopamine similar to 1-methyl-4-phenylpyridinium (MPP + ). The objective of this study was to investigate the effects of MeHg exposure on gene and protein profiles in a dopaminergic MN9D cell line. MN9D cells were treated with MeHg (1-5 μM) and MPP + (10-40 μM) for 48 hr. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…and metalloids. Such studies published these past three years in the Journal of Toxicological Sciences investigated the toxicity of many types of metals, including cadmium (Ohtani et al, 2013;Miura et al, 2013;Baba et al, 2014;Du et al, 2014;Park et al, 2015;Lukkhananan et al, 2015), mercury (Yoshida et al, 2013;Kim et al, 2014), methylmercury (Hwang et al, 2013a(Hwang et al, , 2013bIwai-Shimada et al, 2013;Chang et al, 2013;Hirooka et al, 2013;Kim et al, 2013;Watanabe et al, 2013;Shao et al, 2015;Toyama et al, 2015), aluminum (Zhang et al, 2013;Jinzhu et al, 2015), manganese (Fujishiro et al, 2013), uranium (Lestaevel et al, 2013), arsenic (Tokumoto et al, 2013;Wang et al, 2015), arsine (Kato et al, 2014), organic bismuth (Kohri et al, 2015), chromium (Kimura et al, 2015), and tributyltin (Oyanagi et al, 2015). Although methylmercury is one of the organic-inorganic hybrid molecules (the minimum unit!…”
mentioning
confidence: 99%
“…and metalloids. Such studies published these past three years in the Journal of Toxicological Sciences investigated the toxicity of many types of metals, including cadmium (Ohtani et al, 2013;Miura et al, 2013;Baba et al, 2014;Du et al, 2014;Park et al, 2015;Lukkhananan et al, 2015), mercury (Yoshida et al, 2013;Kim et al, 2014), methylmercury (Hwang et al, 2013a(Hwang et al, , 2013bIwai-Shimada et al, 2013;Chang et al, 2013;Hirooka et al, 2013;Kim et al, 2013;Watanabe et al, 2013;Shao et al, 2015;Toyama et al, 2015), aluminum (Zhang et al, 2013;Jinzhu et al, 2015), manganese (Fujishiro et al, 2013), uranium (Lestaevel et al, 2013), arsenic (Tokumoto et al, 2013;Wang et al, 2015), arsine (Kato et al, 2014), organic bismuth (Kohri et al, 2015), chromium (Kimura et al, 2015), and tributyltin (Oyanagi et al, 2015). Although methylmercury is one of the organic-inorganic hybrid molecules (the minimum unit!…”
mentioning
confidence: 99%
“…previously been described to impair dopaminergic function and to have similar neurotoxic effects to the well-known nigrostriatal toxicant 1-methyl-4-phenylpyridinium (MPP+, the active metabolite of MPTP) (Dreiem et al, 2009;Shao et al, 2015;Tiernan et al, 2015), we decided to focus on TBBPA and berberine chloride and further analyzed them as well as five other compounds of interest in dose-response experiments.…”
Section: High Content Image Analysis Quantified Cell-type-specific Toxicity In 3d Human Midbrain-like Tissuesmentioning
confidence: 99%
“…PD is the second most common neurodegenerative disease and is marked by loss of dopaminergic neurons in the substantia nigra (Alexander, 2004;Poewe et al, 2017). Approximately 90% of cases are of sporadic and idiopathic origin (Lesage and Brice, 2009;Schulze et al, 2018), and many studies hypothesize that genetic and environmental factors, including exposure to toxicants, may play a role in the long-term etiology of PD (Warner and Schapira, 2003;Sulzer, 2007;Goldman, 2014;Bellou et al, 2016;Tysnes and Storstein, 2017). However, Parkinsonism in humans can also have more direct causes, where specific compounds can selectively and acutely ablate dopaminergic neurons.…”
Section: Introductionmentioning
confidence: 99%
“…MeHg impairs the central nervous system, suggesting that MeHg is relevant to the onset of neurodegenerative diseases, such as AD, PD, and ALS [121,122,123,124]. Additionally, it has been reported that MeHg affects fetal neurodevelopment via prenatal exposure to MeHg [125].…”
Section: Mehg and Er Stressmentioning
confidence: 99%